A critique from within: some important research issues that psychologists of religion and spirituality should further work on. Issue 6 (3rd July 2017) - Abu-Raiya, Hisham
ABSTRACT: Operating from a perspective of an empirical psychologist of religion and spirituality, in this paper, I point to some areas of improvement in our field. Specifically, I (1) briefly target the lack of consensus in defining religion and spirituality; (2) point to the need for answering the crucial question: How unique is religion? (3) tackle the Western/Christian bias of the field; and (4) address three fundamental methodological issues (generalisability, self-report, and cross-sectional design) and their implications for research.